Mapeamento do Aquífero Bauru situado sob a zona urbana de Araguari, MG - Segantini, Marília de Oliveira (2010)
This paperwork approaches the main aspects related to the study of the Bauru Aquifer, its exploitation and use, as well as its potentialities in the region of Triangulo Mineiro, in special the city of Araguari, where the main focus of this research took place. The aim is to map the hydrological parameters of the Bauru formation, in the urban limits of Araguari, grouping all data raised by the literature, which were found to be spread over several recent studies. It was also used numerical simulations to determine the downgrades, the flow lines and the water flow speed in the aquifer. The knowledge of the parameters and of the flow in the water source is justified since the aquifer is the primary source of the city. Therefore, a numerical study and flow simulations in the Bauru Aquifer was carried out based on the Finite Difference Model for Unconfined Aquifers, thus allowing the study to be more detailed and precise. In order to mapping the hydrogeological parameters, it were gathered information about 65 wells, located mostly in urban areas, where it was attempted to characterize them with values of hydraulic conductibility, storage coefficient, transmissivity and saturated thickness. The survey included data collection in several scientific papers to consolidate a larger amount of data collection over each well; besides computational tasks, such as interpolation of spatial data and map building of the gathered parameters. The importance of the study, in regional terms is justified because The aquifer Bauru is responsible for 100% of public supply of the city of Araguari, being valid in order to assist future guidelines in managing the aquifer system of the region and take better advantage of its resources, pointing possible saturation places due to exploitation, and better monitoring locations, once the apparent speed of the aquifer groundwater is known.